Texting and Driving: Is It Just Moral Panic?. Issue 11 (2nd November 2018) - White, David R.; Hepworth, Daniel P.; Zidar, Michael S.
ABSTRACT: Significant public efforts have been mounted to stop the perceived epidemic of texting and driving, especially among younger drivers. However, despite the taken-for-granted nature of these fears, cell phones are reported as a contributing factor in only about 1% of all crashes. This study examines 11 years of crash data from Kentucky to demonstrate that despite the exponential growth of cell phones in American culture, cell phone-related crashes have remained stable over time, and they represent far less of a public health risk than most people are led to believe. The conclusions are presented in the context of moral panic theory.